Nilai Kearifan Lokal Tari Teke Pada Masyarakat Suku Lea dan Implementasinya dalam Layanan Bimbingan dan Konseling - Lio, Stefanus Elang; Erlinda, Maria; Margaretha, Dhiu (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
This research explores the significance of local wisdom within the Teke dance of the Lea Tribe community in Degalea Village, Nangaroro District, Nagekeo Regency. We aim to identify how these local wisdom values can be integrated into guidance and counseling services. Our study employs a qualitative research design, utilizing documentation studies, observations, and in-depth interviews with informants and participants as research instruments. Data analysis follows a three-step process: data reduction, data presentation, and drawing conclusions/verification. The findings reveal that the Teke dance embodies local wisdom values such as religious devotion, community togetherness, mutual cooperation, familiarity, and harmony, as evidenced in the choreography. Additionally, the sung poetry reflects local wisdom in family education, personal and social life, and leadership. These discovered values can be integrated into guidance and counseling services to enhance self-awareness and foster healthy, effective behaviors, particularly in addressing deviant behavior, preventing deviations, and promoting personal development within one’s social environment